Placenta Percreta With Bladder Involvement - Zulfiqar, Yefri (Universitas Andalas, 2024)
Placenta accreta spectrum (PAS) is characterized by abnormal placental invasion due to incomplete or complete loss of decidua. PAS subtypes are classified based on the depth of invasion: placenta accreta, increta, and percreta. Placenta percreta is the most severe form of placenta accreta and is characterized by invasion of the placenta through the entire myometrium reaching up to the uterine serosa. The increasing rate of placenta accrete because of increased rate of cesarean delivery. Urological complications are relatively rare in placenta accreta spectrum (PAS), but can be severe. Treatment planning must always involve a multidisciplinary team. Placenta percreta is a very high-risk obstetric condition associated with morbidity and mortality. A 32-year-old woman referred from Maternal Fetal Medicine Polyclinic with G4P2A1L2 37-38 weeks of term pregnancy + total placenta previa suspected percreta PAS 2 grade 3B S2 + once previous CS, and a CCS hysterectomy was planned. PAS with bladder involvement was significantly correlated with massive surgical blood loss. Prenatally, the disorder was predicted with high specificity by the combination of loss of chemical shift artifacts in the steady-state free precession sequence and abnormal vascularization at the uterovesical interface on USG (Ultrasonography)